Literature Review: Analisis Kesiapan dalam Implementasi Berkas Rekam Medis melalui Pendekatan Doq-It - Adinda Nur Aini; Sinta Novratilova; Andhira Deswita Maharani; Affifah Cahya Febriasari; Agnes Mbangi Bangar; Dessyana Dwi Astuti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
The implementation of Electronic Medical Records (EMR) in Indonesia continues to develop as part of the digital transformation in the healthcare sector; however, the readiness of healthcare facilities remains uneven. This study aims to analyze the readiness of EMR implementation using the DOQ-IT approach and to identify supporting factors and barriers. The method used is a literature review with a descriptive qualitative approach on 10 scientific articles published between 2022–2026, obtained from Google Scholar, with a selection process including identification, screening, and eligibility stages. The results indicate that most healthcare facilities are at a moderately ready to highly ready level, although disparities still exist among facilities. The main supporting factors include strong leadership and a supportive organizational culture, while the main barriers consist of limited technological infrastructure, low human resource competence, resistance to change, and suboptimal policies and standard operating procedures. In addition, EMR implementation has been shown to improve service efficiency, the quality of medical documentation, and patient safety. It is concluded that EMR implementation in Indonesia has progressed significantly; however, improvements are still needed in human resources, infrastructure, and governance. Therefore, comprehensive and sustainable strategies are required to optimize EMR implementation across healthcare facilities.